Soil Microbes Drive the Flourishing Growth of Plants From Leucocalocybe mongolica Fairy Ring - Wang, Qiqi; Wang, Chong; Wei, Yumei; Yao, Weiqin; Lei, Yonghui; Sun, Yanfei (Frontiers in Microbiology, 2022)
Fairy ring is a natural phenomenon in which fungal fruiting bodies occur as a ring on a spot. This ring is produced due to spore ejection by Basidiomycetous fungi and forms a lush growing plant belt. However, the drivers for such formations and the potential plant growth-promoting rhizobacteria in fairy ring soils remain unknown. Fairy rings formed by Leucocalocybe mongolica were selected in this study. Soil characteristics and microbial (bacteria and fungi) community structures between beneath and outside the fairy rings were compared through high-throughput sequencing. Beneficial bacterial resources were excavated using dependent culturable methods. Soil electrical conductivity and available potassium were higher in the soil beneath the ring than outside it. These parameters were positively correlated with the dominant microbial community, but microbial diversity was lower. In the soil beneath the fairy ring, Bacteroidetes and Basidiomycota were more abundant, whereas Verrucomicrobia was less prevalent. Bacillus pumilus (strain BG-5) was isolated from the soil beneath the ring. Strain BG-5 can solubilize phosphorus and produce indole-3-acetic acid, NH4+, and siderophores. Furthermore, strain BG-5 enhanced salt tolerance and promoted the growth of Arabidopsis thaliana, wheat (Triticum aestivum), and cotton (Gossypium hirsutum) seedlings. This study indicated the presence of abundant beneficial microbes driving the flourishing growth of plants in the fairy ring soil and provided bio-resources for agricultural growth-promoting agents.